From Seascapes of Extinction to Seascapes of Confidence - Gallardo Fernandez, Gloria L. (Taylor & Francis, 2008)
From Seascapes of extinction to seascapes of confidence. Territorial Use Rights in Fisheries in Chile: El Quisco and Puerto Oscuro by Gloria Gallardo FernandÃ©s is an important contribution to our understanding of the multifaceted challenges underlying sustainable solutions to ecological fisheries, the book describes how, in Chile, indiscriminate harvest of the edible shellfish Concholepas concholepas (false abalone or Loco), has been threatening not only the living of small-scale artisan fishers but also the ecosystem. In an attempt to strengthen the fishersâ€™ livelihoods and at the same time recuperate the fish, the Chilean government introduced the regulatory measure: Management and Exploitation Areas for Benthic Resources (MEABRs), locally known as Management Areas (MAs) and internationally as Territorial Use Rights in Fisheries (TURFs).